Effect of bathocuproine buffer layer in small molecule organic solar cells with inverted structure. (13th March 2015) - Hao, Xia; Wang, Shenghao; Sakurai, Takeaki; Akimoto, Katsuhiro
Abstract: Inverted organic solar cells (OSCs) based on boron subphthalocynine chloride (SubPc) and fullerene (C60 ) were fabricated and the device structure was optimized by inserting a bathocuproine (C26 H20 N2 ) buffer layer. The power conversion efficiency was greatly improved from 0.8 to 1.6%. The roles of bathocuproine in this inverted device were investigated by photoluminescence and transient photovoltage/photocurrent measurements. The results show that the bathocuproine in the device not only blocks the exciton quenching, but also prohibits the build-up of charge trapping and suppresses the trap-assisted recombination.